How Do Early Childhood Teachers Design Lesson Plans? A Professional Competency Analysis - Muktia Pramitasari; Erna Risnawati; Noviana Mustapa; Esti Kurniawati Mahardika; Musakkid Himphinit (Atfaluna: Journal of Islamic Early Childhood Education, 2025)
This study aims to analyze early childhood education (ECE) teachers’ professional competencies in designing lesson plans. A quantitative descriptive approach was employed using a survey method. The participants consisted of 100 ECE teachers from DKI Jakarta and Banten Provinces, selected through purposive sampling. Data were collected using closed-ended questionnaires to measure teachers’ professional competence and open-ended questionnaires to examine the lesson plans prepared by the teachers. The data were analyzed using descriptive statistical techniques. The results indicate that 98% of the ECE teachers were female, with 49% holding a high school qualification and 43% holding a bachelor’s degree. Teachers aged over 50 years demonstrated higher levels of professional competence compared to younger teachers. In terms of educational background, teachers with diploma-level qualifications exhibited higher professional competence than those holding bachelor’s degrees. Teachers with 4–6 years of teaching experience achieved the highest professional competence scores. However, analysis of the lesson plans revealed that most teachers relied heavily on student worksheets, resulting in limited variation and low creativity in learning activities. This study concludes that although ECE teachers demonstrate relatively high levels of professional competence, these competencies are not fully reflected in the quality of their lesson plan design. The findings highlight the need for continuous professional development programs that emphasize creative and innovative lesson planning practices. This study reveals a mismatch between teachers’ measured professional competence and their practical ability to design varied lesson plans within the Indonesian ECE context. Future research is recommended to employ mixed-methods or longitudinal designs to explore the underlying factors influencing this mismatch and to examine the effectiveness of targeted professional development interventions in improving lesson plan quality.